Práticas de cuidado de pessoas com hipertensão arterial sistêmica que vivem no campo - Gomes, Tais Falcão (2016)
Systemic arterial hypertension is a chronic non-communicable disease considered an important public health problem both in the global and national levels. Its repercussions exceed the biological dimension, because, it involves the subjectivity and the social constructions of the person, family and community where they live. Thus, among the scenarios that have been focus of attention and care in health are the ones that comprehend the population that lives in the countryside. It is essential that in these places the care from the cultural perspective is identified and comprehended, allowing the professionals of health to act professionally and efficiently with the people of different cultures. So, it is essential to comprehend the practices of care of people with hypertension that live in the countryside. From this question, we outlined as objective of this study to analyze the way how the people with systemic arterial hypertension that live in the countryside understand and live the practices of care. It is a field research, qualitative, exploratory and descriptive, performed with 13 people with hypertension that live in the countryside, covering the period from May to June of 2015. The data collection was performed by means of participant observation of moderated kind and semi-structured interview. The data was worked by Guide of phases of Data Analysis from the method of etno-nursing suggested by Leininger and McFarland. The research followed the ethical principles of the Resolution number 466/2012 and obtained approval by the Research Ethics Committee with the Approval Certificate for Ethical Assessment number 41156015.7.0000.5346. The results were organized in two categories and three subcategories discussing from the beliefs and experiences in the disease process and the daily care practices. Regarding the experience of living with "high pressure" are revealed trajectories performed to diagnosis, the meanings attributed the etiology of the disease, the changes and the difficulties stemming from living with hypertension, as well as representations of illness resulting from that experience. Also, care practices were discussed from the aspects that concern the habits, uncertainties and possibilities in food, strategies were also identified from the replacement, reduction or elimination partial or total food with potential for worsening health. Another approached practice was the use of medicines and teas as medicines used to control blood pressure levels. Also addressed were the careful design combined with the care practices in general as protection against bad weather, hygiene, interaction with other people, games, leisure activities and social support network as forms of care and welfare. So to understand care practices is critical recognition and appreciation of different existing cultures and the elements present in everyday life.